Hypoxia Immunity, Metabolism, and Hyperthermia. (29th May 2013) - Baronzio, Gianfranco; Kiselevsky, Mikhail; Ballerini, Marco; Cassuti, Valter; Schwartz, Laurent; Freitas, Isabel; Fiorentini, Giammaria; Parmar, Gurdev
Abstract : Hypoxia is common in solid tumors and in many other disease states such as myocardial infarction, stroke, bone fracture, and pneumonitis. Once hypoxia has developed, the undernourished and hypoxic cells trigger signals in order to obtain new blood vessels to satisfy their increasing demands and to resolve hypoxia. The principal signal activated is an ancestral oxygen sensor, the hypoxia inducible factor (HIF). After its nuclear translocation, HIF triggers a series of mediators that recruit, into the hypoxic milieu, several immature myeloid, mesenchymal, and endothelial progenitors cells. Resident and recruited cells participate in the processes of neoangiogenesis, for resolving the hypoxia, while at the same time trigger an inflammatory reaction. The inflammatory reaction has as primary end point, the repair of the damaged area, but if an insufficient production of resolvins is produced, the inflammatory reaction becomes chronic and is unable to repair the damaged tissue. In this brief overview, we will show the differences and the similar events present in cancer, myocardial infarction, and stroke. Furthermore, the metabolic alterations produced in the tumor by hypoxia/HIF axis and the consequences on hyperthermic treatment are also discussed.